2014
DOI: 10.1371/journal.pone.0089863
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Response to Uranyl Exposure at Low pH and Associated Protein Regulations

Abstract: Better understanding of uranyl toxicity in bacteria is necessary to optimize strains for bioremediation purposes or for using bacteria as biodetectors for bioavailable uranyl. In this study, after different steps of optimization, Escherichia colicells were exposed to uranyl at low pH to minimize uranyl precipitation and to increase its bioavailability. Bacteria were adapted to mid acidic pH before exposure to 50 or 80 µM uranyl acetate for two hours at pH≈3. To evaluate the impact of uranium, growth in these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The US Environmental Protection Agency's maximum contaminant limit for U in drinking water is 30 lg L 21 ($0.13 lM), however, groundwater concentrations in the US frequently exceed this limit (Focazio et al, 2006;Hoover et al, 2016). Studies of the U response in anaerobic and aerobic bacteria have revealed a plethora of different stress responses that range from DNA damage, oxidative stress, protein misfolding, to cell envelope stress (Bencheikh-Latmani et al, 2005;Junier et al, 2011;Khemiri et al, 2014, Li et al, 2014. However, the lack of regulatory systems that exhibit a specific response towards U has hindered in-depth mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The US Environmental Protection Agency's maximum contaminant limit for U in drinking water is 30 lg L 21 ($0.13 lM), however, groundwater concentrations in the US frequently exceed this limit (Focazio et al, 2006;Hoover et al, 2016). Studies of the U response in anaerobic and aerobic bacteria have revealed a plethora of different stress responses that range from DNA damage, oxidative stress, protein misfolding, to cell envelope stress (Bencheikh-Latmani et al, 2005;Junier et al, 2011;Khemiri et al, 2014, Li et al, 2014. However, the lack of regulatory systems that exhibit a specific response towards U has hindered in-depth mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanisms used by cells for combating internal U toxicity are poorly understood (14). Previous studies revealed upregulation of metal efflux pumps, NADH quinone oxidoreductases, or other reactive oxygen species (ROS) scavenging enzymes upon exposure to U in the sulfate-reducing bacterium Desulfotomaculum reducens (15), Escherichia coli grown at low pH (16), and the plant Arabidopsis thaliana (17). General and membrane stress responses were particularly pronounced when Shewanella oneidensis was exposed to U (18), and nucleic acid and protein damage have been shown to represent the primary modes of U toxicity in Desulfovibrio alaskensis G20 (19).…”
mentioning
confidence: 99%
“…Previous studies suggest that an increase in pH within a range of 5 to 6 decreases U(VI) bioavailability by lowering the uranyl concentration in aquatic environments (45,46). Consistently, U(VI) complexation by organic or inorganic phosphate was shown to reduce U(VI) toxicity in C. crescentus (14), while lower-pH conditions that favor the presence of the uncomplexed uranyl ion appear to be more toxic to bacteria (47). Further analytical techniques will be required to substantiate a speciation dependency of U(VI) toxicity in our system.…”
Section: Discussionmentioning
confidence: 63%